Determining solid/liquid interfacial energies in Al-Cu by curvature controlled melting point depression. (1st April 2018) - Lippmann, S.; Simon, C.; Zechel, S.; Seyring, M.; Schubert, U.S.; Wilde, G.; Rettenmayr, M.
Abstract: An experimental method for determining solid/liquid interfacial energies of alloys is presented. Spherical intermetallic particles of Al2 Cu with diameters down to 50 nm were generated as "divorced eutectic" in an initially homogeneous solid solution of 4 wt% Cu in Al by short-term annealing (t < 10 s) in a temperature gradient. Particle size distributions were analyzed using transmission electron microscopy (TEM) after dissolving the Al matrix of a representative part of the sample in dry butanol. During heating of the remaining sample part in a highly sensitive power-compensating differential scanning calorimeter, the onset of eutectic melting was measured. The expectation value of the narrow size distributions and the respective curvature undercooling were correlated on the basis of the Gibbs-Thomson equation. For deriving the solid/liquid interfacial energy, the temperature and concentration dependent melting entropy were calculated under the assumption of thermodynamic equilibrium at the solid/liquid interface using a CALPHAD type database. In thermodynamic equilibrium, at a constant temperature the solid and the liquid phase have different concentrations at the interface leading to an interfacial energy that is higher than the value for pure Al derived from maximum supercooling experiments, and lower than the value for Al-Cu determined using the grain boundary groove method. The extension of the method to other alloy systems is discussed. Graphical abstract: Image 1